Rethinking surgical success in non-cancer operations—why patient experience must lead - Jacob Rosenberg; Anders Gram-Hanssen; Hugin Reistrup; Jason Joe Baker (Journal of Patient-Reported Outcomes)
Abstract Background Traditionally, surgical success in non-cancer operations, such as elective hernia repair, has been defined by clinical outcomes, including recurrence and complication rates. However, these measures do not capture the primary reason patients seek surgery: relief from symptoms and an improved quality of life. Despite the evident patient-centered goal of non-cancer surgical procedures, research has long prioritized clinical parameters over patient-reported outcomes (PROs). A shift is essential to ensure that surgical success aligns with what truly matters to patients. Main body Current surgical research and practice heavily rely on clinical benchmarks that do not adequately reflect patients’ lived experiences. For non-cancer conditions, where surgery is elective and aims to enhance quality of life, PROs should serve as the primary indicators of success. Studies across various surgical disciplines have revealed discrepancies between clinical outcome measures and patient satisfaction, highlighting the need for validated, standardized PRO instruments. The Danish AFTERHERNIA Project exemplifies efforts to integrate PROs into surgical evaluations, utilizing digital health infrastructure to systematically capture patient experiences. Additionally, condition-specific tools, such as the Abdominal Hernia-Q, demonstrate the growing recognition of patient-centered metrics. However, the widespread implementation of PRO measurement faces challenges, including resource constraints and the need for clinician training. Addressing these barriers is important for redefining success in non-cancer surgical care. Conclusions A paradigm shift in non-cancer surgical evaluation is important. Success should be measured not only by technical outcomes but also by enhancements in patient-reported quality of life and satisfaction. Incorporating PROs into surgical research and practice is both a scientific necessity and an ethical responsibility to ensure that patient needs are addressed. Moving forward, the patient experience must become the foundation for defining surgical success in non-cancer conditions. Ultimately, the primary objective of surgical intervention should be to improve the patient’s health status and overall well-being compared to their preoperative condition.